2021
DOI: 10.12659/ajcr.933462
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoids Induce Partial Remission of Focal Segmental Glomerulosclerosis but Not Interstitial Nephritis in COVID-19 Acute Kidney Injury in an APOL1 Low-Risk Genotype White Patient

Abstract: Patient: Male, 34-year-old Final Diagnosis: Focal segmental glomerulosclerosis Symptoms: Acute kidney injury • nephrotic syndrome Medication: — Clinical Procedure: Kidney biopsy Specialty: Nephrology Objective: Rare coexistence of disease or pathology Background: COVID-19 can be complicated by kidney disease, including focal segmental glomerulosclerosis (FSGS), interstitial nephritis, and acute kidn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 29 publications
(71 reference statements)
0
1
0
Order By: Relevance
“…Despite that, our patient developed mild COVID a few months after her initial flare of proteinuria and did not require any treatment or hospitalization. FSGS in our patient was discovered with her flares of RA, unrelated to the time of her COVID infection, which makes COVID-19 less likely the culprit of her nephrotic syndrome compared to her RA diagnosis of 30 years [27].…”
Section: Case/yearmentioning
confidence: 72%
“…Despite that, our patient developed mild COVID a few months after her initial flare of proteinuria and did not require any treatment or hospitalization. FSGS in our patient was discovered with her flares of RA, unrelated to the time of her COVID infection, which makes COVID-19 less likely the culprit of her nephrotic syndrome compared to her RA diagnosis of 30 years [27].…”
Section: Case/yearmentioning
confidence: 72%
“…Nowak et.al. [40] demonstrate that an unproportional immune response to the virus antigens may lead to cytokine storm, interferon release and mononuclear cells activation resulting in kidney inflammatory injury.…”
Section: Detection Of Coronaviruses In Renal Tissuesmentioning
confidence: 93%
“…ACE2 is widely expressed not only in the lungs, but also in other vital organs such as the kidney, and it interacts with viral spike protein [21]. However, it is still being questioned whether the kidney damage is directly mediated by presence of the virus or by a secondary to immune response [40]. Diao et al [21] showed that SARS-CoV-2 nucleocapsid protein and spike antigens were found binding the ACE2 protein in the kidney tubules.…”
Section: Detection Of Coronaviruses In Renal Tissuesmentioning
confidence: 99%